At-Tawaruq al-Mushrifi wa Masru'iyatuhu - Rouyani Anwari (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2013)
Tawarruq is currently a hot topic of conversation among academics as well as sharia finance practitioners. This paper explains specifically about Tawarruq Mashrofi in Islamic banking. There are at least three Tawarruq formations discussed in this article, namely (1) Someone who needs liquidity (money cash) buy products/goods/commodities from sharia banks using credit and sell it to another party for cash, without the other party knowing the intention is as stated above) 2( A person (mutawarriq) who needs money cash, asked to be given a loan from a sharia bank, then the party banks offer goods/commodities/products for sale to other parties at a lower or higher price in cash. Proceeds from that sale given to mutawarriq as a loan to be repaid on credit; (3) Almost the same as formation number 2, but the bank sells the goods at a price higher than the market price to Mutawarriq, as a result of delayed payments/in installments. This formation is still being debated by sharia economic law experts.